THE INFLUENCE OF THE IMPLEMENTATION OF THE PROGRAM OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AGAINST THE IMAGE OF THE COMPANY PT. ARARA ABADI ON SOCIETY PERAWANG KEC. TUALANG KAB. SIAK - Rahman, Abdul; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Many companies are increasingly aware of and assessing the implementation or application of CSR programs not merely fulfill the obligations as set out in the Act. The better a company'S CSR program implementation the more positive and also good corporate image in the eyes of the public . The application of CSR program PT. Arara Abadi held already although there is still that have not been fully implemented as expected community so that the positive image that was expected by the company has not achieved fully.This research was conducted at the Subdistrict Perawang Tualang Siak Regency. As for the reason for choosing a PT. Arara Abadi that to measure the degree of implementation of CSR and decline the positive image of the company. The purpose of this research was conducted to find out the influence of the implementation of the program of corporate social responsibility (CSR) against the company's image.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sample used by that is community around company society perawang and as source of information is party of UP-CD CSR PT.Arara Abadi. To determine sampel use formula Slovin, method of sampling by accidental sampling. Technics of data collecting of through, observation and quesioner.From the results of the data analysis that includes a test of validity, reabilitas, and a simple linear regression, the implementation of CSR programs against the corporate image. Each has interconnected indicators and positive effect toward corporate image on PT. Arara Abadi Perawang.Keyword: The implementation of CSR programs and corporate image